العنف ضد المرأة وعلاقته بالألم النفسي لموظفات جامعة بغداد (Journal Of Educational and Psychological Researches, 2017)
The current research aims at identifying the level of violence against women and relationship with psychological pain according to social status . To achieve the aims of the study a sample has been chosen to be (200) employers distributed to five colleges at Baghdad university. The violence scale which consists of (23) items in its final from , and the psychological pain scale which consists of (30) items in its final form and extracted validity and reliability of the scale the findings of the study include the following :- • The employers of Baghdad university don’t have any violence.• The employers of Baghdad university don’t have any psychological pain . • There was relationship between the violence and psychological pain.• The difference in violence comparisons according to the social status to the benefit of the divorced women. the light of the findings the researcher set numbers of recommendations and suggestions.